A New Security Passcode Approach for Alzheimier Patient based on GeoLocation Identification - Amir Adhwa Afiq, Samsuri; Mohamad Fakhruddin, Mustafa; Nor Azhar, Ahmad (Faculty of Computer Systems & Software Engineering, Universiti Malaysia Pahang, 2016)
Alzheimer disease is one of the common syndromes categorized under dementia cases. In some records, it shows that this illness can’t be cured even 10 to 20 years of procedure. The common symptoms that suffered by the patients are amnesia or loss of memory and ability to thinking correctly [1] [4]. This syndrome may also affect family members, friends, and also some others institution like a company that implements security authentication system. Nowadays, as we can see, no special password authentication system should provide to Alzheimer’s patients. Due to lack of authentication technology, there is a need for developing password authentication system, especially for Alzheimer’s patients. This document would discuss how to develop a new security passcode approach that can use by the Alzheimer’s patients with the assist of geolocation identification method.